Research of the methods for improving performance for cryptographically strong BBS pseudorandom bit sequences generators - Malohlovets, Andrii; Maxymovych, Volodymyr (Lviv Polytechnic Publishing House, 2016)
The aim of this work is the research of methods for improving the performance on cryptographically strong BBS generators, their practical realization and analysis of their efficiency.
Keywords: BBS; improving performance; computational complexity; efficiency of parallelizing; K-stream generator